The Role of Digitizing Museum Collections as a Strategic Effort to Deepen Educational Insights into the Influence of History in the Modern Era - Daffa, Rayhan Faza Surya; Khoirunisa, Putri (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
In the digital age, history education is often limited to online sources such as Google, academic articles, and AI. However, studying history requires fieldwork, such as examining primary archives, researching artifacts, and receiving direct instruction from historians with extensive experience in historical research. This study aims to examine the role of museums as digital-based historical education platforms. In this research, we employed qualitative methods, including literature review and observations at several museums. The findings indicate that museums serve not merely as repositories for historical artifacts but as providers of various digital tools, making them attractive tourist destinations for visitors. These include a variety of historical illustrations that can be scanned into 3D as tools for cool and aesthetically pleasing selfies and videos to document memorable visits. There are also digital displays that feature historical descriptions for each collection of historical artifacts, as well as digitized pages from manuscripts. Museum docents play a crucial role in guiding visitors, providing education on the interpretation of digital records, explaining the museum’s collection of historical artifacts, and demonstrating the museum’s engaging digital features, all of which enhance the visitor experience.